Impactos da urbanização na ictiofauna de riachos na parte superior da bacia do Alto Rio Paranapanema (SP), Brasil - Peressin, Alexandre (2013)
Aquatic ecosystems have suffered strong anthropogenic pressure, through the construction of dams, water exploitation, chemical pollution, destruction of the surrounding environment, especially riparian vegetation, and structural changes such as channeling and siltation. Fish assemblages may respond in different ways to these environmental changes, because species exhibit different constraints, e.g., habitat demands, physiological tolerance. Thus, some species may be favored in detriment of others. Aware of the need to understand and identify the patterns response of fish assemblages and individual organisms to impact factors, this study aimed to investigate how fish biodiversity (i.e., assemblages and population-scale) respond to urbanization. Fish samples were collected in four stretches located in urban areas and six located in non-urban areas of the upper Paranapanema river basin. Chapter I focused on detecting changes in physical habitat variables, structure and composition of the fish assemblage. Multivariate analyses ordered stretches in a urbanized non urbanized gradient. Non urbanized stretches exhibited greater values of shading, vegetated surronding and coarser substrate. Assemblage structure, i.e., Shannon diversity index, Pielou evenness and Margalef richness, did not change in response to urbanization, as well as the relationship between abundance and biomass. In contrast, assemblages composition was different, as well as richness estimates based on rare species, which was lower in urban stretches. The patterns herein obtained illustrate the process of species replacement, already demonstrated in disturbed environments, in which species pre-adapted to the new conditions increase in abundance, while otherspreviously absent establish successfully. Therefore, diversity values maintain, but composition varies. In general, midwater omnivorous species were more abundant in urban areas, while loricarids and benthic invertivores presented higher average abundance in nonurban stretches. Chapter II aimed to identify changes in the trophic structure, substrate composition and its influence on trophic structure and body condition. For this, species diet was quantified according to the Degree of Food Preference (DFP) method, based on six items: plant material, algae, detritus, invertebrates, insects and fish. According to the items consumed, species were classified in trophic groups. Fourteen species were considered invertivorous/detritivorous, seven herbivorous/detritivorous, seven omnivorous and one piscivorous. Four invertivores/insectivores were exclusive of nonurban stretches and one species exclusive of urban stretches. Three herbivores/detritivores were exclusive of the nonurban stretches, whereas three omnivores were exclusive to urban stretches. Trophic structure richness, abundance and biomass were compared between urban and nonurban stretches. Abundance was not affected by urbanization, whereas richness and biomass varied between stretch groups. Substrate composition differed according to stretch type, and was positively related to invertivores/insectivores and herbivore/detritivores richness, whereas negatively related to omnivore biomass. These results suggest complex relationships between food availability, trophic plasticity and species foraging habits. It is known that coarser substrates such as rocks, branches and trunks are useful as surface for periphyton algae growth as well as shelters for aquatic macroinvertebrates. Thus, changes in substrate may alter resources availability for certain species. Omnivores, in turn, can find other sources of food items due to its trophic plasticity. In general, almost all species absent from urban stretches exhibit some trophic specialization and often depend on heterogeneous substrate for foraging. Moreover, species exclusive to urban stretches are mid-water foragers that do not depend on substrate and present high trophic plasticity. Our conclusions were supported by Astyanax fasciatus body condition analysis, an omnivorous nektonic species which demonstrated higher mean weight in urban stretches, when discounted length.